2010
DOI: 10.1002/chem.200902406
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates Involved in the Oxidation of Nitrogen Monoxide: Photochemistry of the cis‐N2O2⋅O2 complex and of sym‐N2O4 in Solid Ne Matrices

Abstract: Pure sym-N(2)O(4) isolated in solid Ne was obtained by passing cold neon gas over solid N(2)O(4) at -115 degrees C and quenching the resulting gaseous mixture at 6.3 K. Filtered UV irradiation (260-400 nm) converts sym-N(2)O(4) into trans-ONONO(2), a weakly interacting (NO(2))(2) radical pair, and traces of the cis-N(2)O(2)O(2) complex. Besides the weakly bound ONO(2) complex, cis-N(2)O(2)O(2) was also obtained by co-deposition of NO and O(2) in solid Ne at 6.3 K, and both complexes were characterised by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 116 publications
(325 reference statements)
0
30
0
Order By: Relevance
“…The IR difference spectrum showing the change of the matrix upon photolysis is given in Figure . Almost 80 % of OCNSO decomposed after 20 minutes of irradiation, no isomers (e.g., O 2 SNC, O 2 SCN, and OSOCN, Table S2 in the Supporting Information) but only the fragmentation species CO, OSN/SNO, OCS, and NO were identified. Therefore, similar to the photo‐induced CO elimination of covalent isocyanates, OCNSO eliminates CO and furnishes OSN, and the latter undergoes photoisomerization into SNO .…”
Section: Methodsmentioning
confidence: 99%
“…The IR difference spectrum showing the change of the matrix upon photolysis is given in Figure . Almost 80 % of OCNSO decomposed after 20 minutes of irradiation, no isomers (e.g., O 2 SNC, O 2 SCN, and OSOCN, Table S2 in the Supporting Information) but only the fragmentation species CO, OSN/SNO, OCS, and NO were identified. Therefore, similar to the photo‐induced CO elimination of covalent isocyanates, OCNSO eliminates CO and furnishes OSN, and the latter undergoes photoisomerization into SNO .…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies 29–31 observed the formation of the intermediate NO 3 at atmospheric pressure, at ambient temperature, and at lower temperatures. On the other hand, Beckers et al 32 came to the conclusion that the nitric oxide oxidation mechanism involving the nitric oxide dimer (NO) 2 then the formation of various N 2 O 4 species from the N 2 O 2 . O 2 complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At first, arylsilver complex C is formed via coordination of silver catalyst to the acetylamino directing group,[33b] which subsequently provides N ‐phenyl acetamide radical D and Ag 0 which is reoxidiszed to Ag I in presence of K 2 S 2 O 8 . Intermediate D reacts with in situ generated NO 2 radical, , to give the ortho ‐nitrated product 2b . To prove the radical mechanism, a control reaction was carried out using 2,6‐di‐ tert ‐butyl‐4‐methylphenol (BHT) as a radical scavenger.…”
Section: Resultsmentioning
confidence: 99%